Prevalence of celiac disease in children with type 1 diabetes mellitus and the accuracy of serological tests - ÖZDEMİR, HÜLYA (My University, 2018)
In children with type 1 diabetes mellitus (DM), prevalence of some autoimmune diseases like celiac disease (CD) has been increased. It is also reported that CD often can be asymptomatic and only serologically evident in patients with type 1 DM. In our study, we aimed to investigate the prevalence of asymptomatic CD and the specificity and sensitivity of anti-gliadin antibodies (AGA), anti-endomysium (EMA) and tissue transglutaminase (tTG) antibodies that used for diagnosis of CD in these patients. Anti-gliadin-IgA, AGA-IgG, EMA, tTG-IgA levels were evaluated. Small-intestine biopsies were applied to the children that parents were positive for at least one of AGA-IgA, AGA IgG, EMA and tTG-IgA. A total of 268 Type 1 DM children were included in the study. Of these sixty-four children who had at least one serological positive underwent small intestine biopsies and in five children (1.9%) CD was diagnosed. Anti-endomysium and tTG-IgA positivity were detected in all cases with Celiac disease, and sensitivity was 100% for both and 95% and 86% for specificity, respectively. The sensitivity and specificity of anti-endomysium and tTG-IgA antibodies were considered to be the most reliable indicator because of their higher specificity than other serological tests. Our results, which support current guidelines, suggest that children with Type 1 DM can be screened with tTG-IgA and EMA, which are the most sensitive and specific tests to detect asymptomatic CD in these patients.
Keywords: Biyoloji; Alerji; Anatomi ve Morfoloji; Androloji; Anestezi; Odyoloji ve Konuşma-Dil Patolojisi; Biyokimya ve Moleküler Biyoloji; Biyofizik; Biyoteknoloji ve Uygulamalı Mikrobiyoloji; Kalp ve Kalp Damar Sistemi; Hücre Biyolojisi; Klinik Nöroloji; Yoğun Bakım, Tıp; Dermatoloji; Acil Tıp; Endokrinoloji ve Metabolizma; Gastroenteroloji ve Hepatoloji; Geriatri ve Gerontoloji; Sağlık Bilimleri ve Hizmetleri; Hematoloji; İmmünoloji; Enfeksiyon Hastalıkları; Tamamlayıcı ve Entegre Tıp; Tıbbi Etik; Tıbbi İnformatik; Tıbbi Laboratuar Teknolojisi; Genel ve Dahili Tıp; Adli Tıp; Tıbbi Araştırmalar Deneysel; Mikrobiyoloji; Nörolojik Bilimler; Kadın Hastalıkları ve Doğum; Onkoloji; Göz Hastalıkları; Ortopedi; Kulak, Burun, Boğaz; Patoloji; Pediatri; Periferik Damar Hastalıkları; Fizyoloji; Temel Sağlık Hizmetleri; Psikiyatri; Halk ve Çevre Sağlığı; Radyoloji, Nükleer Tıp, Tıbbi Görüntüleme; Rehabilitasyon; Solunum Sistemi; Romatoloji; Spor Bilimleri; Cerrahi; Transplantasyon; Tropik Tıp; Üroloji ve Nefroloji